2021
DOI: 10.1002/chem.202103857
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis, Configurational Assignment and Biological Evaluations of the Lipid Mediator RvD2n‐3 DPA

Abstract: Herein we report the first total synthesis of RvD2n‐3 DPA, an endogenously formed mediator biosynthesized from the omega‐3 fatty acid n‐3 docosapentaenoic acid. The key steps are the Midland Alpine borane reduction, Sonogashira cross‐coupling reactions, and a Z‐selective alkyne reduction protocol, yielding RvD2n‐3 DPA methyl ester in 13 % yield over 12 steps (longest linear sequence). The physical property data (UV chromophore, chromatography and MS/MS fragmentation) of the synthetic lipid mediator matched tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 47 publications
(83 reference statements)
1
18
0
Order By: Relevance
“…The stereochemistry of RvD1was proved to be 7S,8R,17S-trihydroxy-4Z,9E,11E,13Z,15E,19Z-docosahexaenoic acid, and that of AT-RvD1 was established as 7S,8R,17R-trihydroxy-4Z,9E,11E,13Z,15E,19Z-docosahexaenoic acid [93] .Furthermore, the second pathway for biosynthesis of RvD1 and AT-RvD1 involves the oxygenation of 17-hydro(peroxy) product at the C-7 position by 5-LOX to yield 17S-hydro(peroxy)-7S-HDHA, which is then converted by enzymatic epoxidation to16,17S-epoxy-7S-HDHA intermediate. This 16(17)-epoxide upon enzymatic hydrolysis at C-1,10 yields RvD1, or AT-RvD1 if acetylated COX-2 is involved [108] , [109] .Additionally, RvD1 n-3 can be synthesized from 7(S),17(S)-diHpDPA, which is enzymatically converted to 7S,8R-epoxy 17S-HDPA,an epoxide intermediate,which upon hydroxylation yields RvD1 n-3 [110] . The complete stereochemistry of RvD1 n-3DPA is 7S,8R,17S-trihydoxy-9E,11E,13Z,15E,19Z-docosapentaenoic acid [111] .…”
Section: Specialized Pro‑resolving Lipid Mediators (Spms)mentioning
confidence: 99%
See 2 more Smart Citations
“…The stereochemistry of RvD1was proved to be 7S,8R,17S-trihydroxy-4Z,9E,11E,13Z,15E,19Z-docosahexaenoic acid, and that of AT-RvD1 was established as 7S,8R,17R-trihydroxy-4Z,9E,11E,13Z,15E,19Z-docosahexaenoic acid [93] .Furthermore, the second pathway for biosynthesis of RvD1 and AT-RvD1 involves the oxygenation of 17-hydro(peroxy) product at the C-7 position by 5-LOX to yield 17S-hydro(peroxy)-7S-HDHA, which is then converted by enzymatic epoxidation to16,17S-epoxy-7S-HDHA intermediate. This 16(17)-epoxide upon enzymatic hydrolysis at C-1,10 yields RvD1, or AT-RvD1 if acetylated COX-2 is involved [108] , [109] .Additionally, RvD1 n-3 can be synthesized from 7(S),17(S)-diHpDPA, which is enzymatically converted to 7S,8R-epoxy 17S-HDPA,an epoxide intermediate,which upon hydroxylation yields RvD1 n-3 [110] . The complete stereochemistry of RvD1 n-3DPA is 7S,8R,17S-trihydoxy-9E,11E,13Z,15E,19Z-docosapentaenoic acid [111] .…”
Section: Specialized Pro‑resolving Lipid Mediators (Spms)mentioning
confidence: 99%
“…This SPM is formed after two consecutive lipoxygenation reactions, first lipoxygenation occurs via 15-LOX and forms 17(S)-HpDPA, while the second lipoxygenation step occurs in the presence of 5-LOX and yields 7(S),17(S)-diHpDPA and epoxide formation, followed by ring opening of the epoxide by a hydrolytic enzyme. The stereochemistry of this oxygenated SPM was established as RvD2 n-3 DPA 7S,16R,17S-trihydroxydocosa-8E,10Z,12E,14E,19Z-pentaenoic acid [110] , [115] .…”
Section: Specialized Pro‑resolving Lipid Mediators (Spms)mentioning
confidence: 99%
See 1 more Smart Citation
“…These reactions were among the first examples of water-mediated desymmetrization reactions. Half-esters produced in these reactions are very versatile building blocks applied to the synthesis of pharmaceuticals, natural products, and polymers. These reactions can produce the corresponding half-esters even in near-quantitative yields in many cases.…”
Section: Introductionmentioning
confidence: 99%
“…As of today, stereoselective total syntheses of RvD1 n‑3 DPA and RvD2 n‑3 DPA have been achieved (Figure ). Recently, it was reported that RvD5 n‑3 DPA ( 1 ) binds to and activates GPR101, exerting tissue-protective actions during inflammatory arthritis .…”
mentioning
confidence: 99%